2011
DOI: 10.1093/aje/kwr062
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Arsenic Exposure From Drinking Water and Incidence of Skin Lesions in Bangladesh

Abstract: Elevated concentrations of arsenic in groundwater pose a public health threat to millions of people worldwide. The authors aimed to evaluate the association between arsenic exposure and skin lesion incidence among participants in the Health Effects of Arsenic Longitudinal Study (HEALS). The analyses used data on 10,182 adults free of skin lesions at baseline through the third biennial follow-up of the cohort (2000-2009). Discrete-time hazard regression models were used to estimate hazard ratios and 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 46 publications
4
125
0
3
Order By: Relevance
“…They were reported to occur from exposure to concentrations as low as 10 μg/L in prospective cohort studies (Argos et al, 2011). The median frequency of skin lesions in subjects chronically exposed to As was shown to be 32.43% in the province of Tucumán in 2009-2014.…”
Section: Discussionmentioning
confidence: 99%
“…They were reported to occur from exposure to concentrations as low as 10 μg/L in prospective cohort studies (Argos et al, 2011). The median frequency of skin lesions in subjects chronically exposed to As was shown to be 32.43% in the province of Tucumán in 2009-2014.…”
Section: Discussionmentioning
confidence: 99%
“…the earliest, often FIGURE 4 Incidence of skin lesions (dotted line) and bladder cancer (unbroken line) in relation to exposure to arsenic in drinking water. Incidence (above-background incidence) of skin lesions (keratosis and melanosis) per 9 years of exposure is estimated from Argos et al (2011). Incidence of bladder cancer in life-long exposure is estimated from data by Chen et al (2010), modeled by Carrington et al (2013), and with background incidence subtracted.…”
Section: Risk Characterizationmentioning
confidence: 99%
“…2 In this study, most of skin cancers were found both in the exposed and covered areas and the lesions in the covered areas outnumbered the sun-exposed areas. Arsenical basal cell carcinomas most often arise from the normal tissue, frequently occur on the trunk.…”
Section: Discussionmentioning
confidence: 50%
“…Arsenical basal cell carcinomas most often arise from the normal tissue, frequently occur on the trunk. 2 In this study, among the 3 basal cell carcinoma, 2 were found on the trunk and one in the palm.…”
Section: Discussionmentioning
confidence: 52%